Impact of culture on Social Media usage within public - private organizations using Technology Acceptance Model - Mohsin Ali, Rana; Bali Mahomed, Anuar Shah; Raja Yusof, Raja Nerina (Publications International, 2017)
Social Media and other web technologies have experienced an extraordinary rate of growth over the past few years. This conceptual paper aims to propose the innovative link between Corporate Culture and Social Media usage, supported by Technology Acceptance Model. For the sake of content sharing and social networking, Social Media has gained so much presence everywhere, over recent years. Substantially, technology is socially and culturally fashioned in such a way that it cannot be detached from human beings. To understand the link between the culture and usage of Social Media,, respondents from Malaysian Public and Private Universities are identified to explain this relationship. In this regard, a questionnaire will be developed from reliable scales. This study adopts Technology Acceptance Model by Davis (1989) as its supporting framework to theorize the relationship between Perceived Usefulness and Perceived Ease of Use. This research will contribute towards bridging the gap that exists in the literature regarding using of Social Media in public and private organizations. This study will be helpful in attaining the stated objectives. Specifically this study will contribute towards the provision of the evidence of Social Media usage amongst public and private organizations, provision of the evidence if culture influences Social Media usage, provision of the evidence on the mediating effects of Technology Acceptance Model between corporate culture and Social Media usage, provision of knowledge that might allow stakeholders to increase the application of Social Media communication which in turn can produce considerable economic benefits.